Role of Parathyroid Hormone Level as a Predictive Marker for Postoperative Hypocalcemia after Total Thyroidectomy - Inayat Husain Anjum, Syed Aqeel Abbas Kazmi, Omer Farooq, Muhammad Zafar Mengal, Muhammad Tariq Nazir, Arif Khurshid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypocalcemia is a common and potentially serious complication after total thyroidectomy (TT) for thyroid cancer. Parathyroid hormone (PTH) levels have been suggested as a potential predictor for hypocalcemia after the procedure, but their clinical value remains uncertain. Objective: This study aims to evaluate the role of PTH levels as a predictive marker for postoperative hypocalcemia following TT for thyroid cancer. Methods: This cross-sectional study was conducted on 120 patients who underwent TT for thyroid cancer at the Department of Surgery Sahara Medical College, Narowal. The study duration was one year from July 2022 to June 2023. Serum PTH levels were measured at various time points postoperatively, and their correlation with the development of hypocalcemia (defined as a calcium level below 8.5 mg/dL) was analyzed. The primary endpoint was the association between PTH levels and the occurrence of hypocalcemia within the first 48 hours post-surgery. SPSS version 21 was used to analyze the data. Results: Among the 120 patients, 40 (33.3%) developed hypocalcemia. The mean PTH level at 24 hours post-surgery was significantly lower in patients who developed hypocalcemia compared to those who did not (12.4 pg/mL vs. 26.7 pg/mL, p < 0.05). Receiver operating characteristic (ROC) curve analysis identified a PTH level threshold of 15 pg/mL as the most accurate predictor of postoperative hypocalcemia, with a sensitivity of 85% and specificity of 75%. Conclusion: Postoperative PTH levels are a significant predictor of hypocalcemia following TT for thyroid cancer. Monitoring PTH levels early in the postoperative period can help identify patients at higher risk for hypocalcemia, allowing for timely management and improved patient outcomes. Keywords: Parathyroid hormone; Predictor; Hypocalcemia; Total thyroidectomy